INTERNAL CONFLICT MANAGEMENT OF NATIONAL TRADE UNION ORGANIZATION WITH INTERPERSONAL APPROACH IN DPC SPN SERANG REGENCY - Asep Saepulloh; April Laksana (SEAN Institute, 2022)
Globalization is causing changes, and future challenges signal organizations to always make adaptable adjustments in various aspects. The organization is formed from various perspectives of its critical thinkers, which makes it continue to grow in every movement. The purpose of organizational communication is to facilitate, implement, and smooth the course of the organization. The executive order in the National Trade Union (SPN) is an organization that struggles for workers and workers in appreciating complaints and providing contributions. Internal organizational conflicts begin with disputes and differences in assumptions and perceptions between the board and its members in the trade union organization. Conflicts occur in interpersonal relationships where a person's actions or goals are disrupted, hampered, or hindered by others due to a conflict of interests or needs within the organization. The research that has been developed is by the results of observations in the field using Descriptive Qualitative assessment from each SPN Trade Union Leader (PSP) company. Conflict Management uses an interpersonal communication approach and carries out approach strategies to avoid Conflict in the organization. Efforts and efforts are one key to reflecting on organizational refreshment by using good and effective organizational communication with members, administrators, and the structural organization of the National Trade Union in Serang Regency, which is maintained in a coordinated and effective manner with the SPN Trade Union Leader (PSP) in each Company.